Template-free synthesis of large anisotropic gold nanostructures on reduced graphene oxide - Wang, Jing (2013)
The morphologies/dimensions of Au nanostructures can be tailored by merely controlling the reduction degree of graphene oxide surface. Au nanoparticles, long Au nanowires, and semicircular-shaped Au nanoplates are in situ synthesized on slightly, moderately, and highly reduced graphene oxide films respectively, without the need of any templating agent.